Eksperimentasi Pembelajaran Realistik ditinjau dari Aktivitas Belajar Siswa pada Materi Segiempat - Dewi Azizah (Universitas Pekalongan, 2013)
The purpose of the research was to describe the differences between Realistic Mathematics Education and Mechanistic learning approach in mathematics achievement viewed from students’ activity. The research was a quasi experimental. The population of the research was all the seventh grade students of junior high school in Pekalongan regency. The instruments used to collect the data were achievment on quadrilateral topic and questionnare of the students activity in learning mathematics. To analyze the data, the researcher used anova (analysis of variances) with unbalanced cells. It was concluded that Realistic Mathematics Education gave a better result than Mechanistic learning approach on quadrilateral topic and the students mathematics achievement for the students that high activity was better than those who had a moderate and low activity, whereas the students mathematics achievement that had a moderate activity was equivalence to the students who had a low activity.